Sosialisasi Manajemen Waktu guna Meningkatkan Keterampilan Belajar Siswa Sekolah Dasar - Ryan Agustin; Muhammad Abdil Fahriza; Rizky Fadillah; Sandy Firdaus; Sahra Wardi; Sudirwo Sudirwo; Anna Nur Faidah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aimed to socialize time management materials to sixth-grade elementary school students in order to improve their learning skills, productivity, and sense of responsibility during their educational process. The activity was conducted at SDN Inti Sungai Miai 11, Banjarmasin, on September 19, 2025, with 34 student participants consisting of 17 boys and 17 girls from combined classes VI A and VI B. The method used was an interactive socialization approach that began with a pre-test and ended with a post-test using questionnaires to measure changes in students’ understanding and attitudes, followed by the delivery of materials, question-and-answer sessions, active discussions, and a brief practice of preparing a daily study schedule with a student representative. Quantitative results showed an increase in the average score of students’ understanding from 2.43 to 2.48, with a difference of 0.05, particularly in the indicator of ability to create a daily schedule, which increased by 0.29. In addition, qualitative results indicated an increase in students’ awareness and behavioral changes in managing their time more regularly during school activities. This activity had a positive impact on fostering students’ discipline and responsibility, and it is recommended that time management activities be integrated sustainably into school learning programs and curriculum.